An equivalent media theory for reservoir characterization - Prajapati, S. (International Petroleum Technology Conference (IPTC), 2019)
The existence of elastic anisotropy in the reservoir is obtained through the equivalent media theory. An isotropic elastic theory fairly explains the reservoir modeling or characterization but its not well explain anisotropic characteristic fairly for reservoir characterization which is extremely challenging without considering a self-consistent theory of effective equivalent media theory. In this research, equivalent media theory has been explained and implemented on a producing well-log data with consistent Vp, Vs, density and other parameters. Instead of using Voigt averaging, equivalent media theory used to estimate the effective stiffness parameters and compare with Thomsen's parameters and finally used effective anisotropy parameters and compare with gamma log. Result shows the effectiveness of equivalent media theory for future application for developing reservoir modeling and characterization. Â© 2019, International Petroleum Technology Conference